2022
DOI: 10.3389/fnagi.2022.791971
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Longitudinal Study of Frailty and Depressive Symptoms Among Older Chinese Adults

Abstract: ObjectiveFrailty and depression, as two common conditions among older adults in China, have been shown to be closely related to each other. The aim of this study was to investigate the bidirectional effects between frailty and depressive symptoms in Chinese population.MethodsThe bidirectional effect of frailty with depressive symptoms was analyzed among 5,303 adults ≥ 60 years of age from the China Health and Retirement Longitudinal Study (CHARLS). Phenotype and a frailty index were used to measure frailty. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
1
8
1
Order By: Relevance
“…The ndings of this study were consistent with a number of earlier ndings, which indicated that frailty in the middle-aged and elderly Chinese population predicted the development of depressive symptoms [17,31] . Meanwhile, frailty was found to be a predictor of depressive symptoms in a cross-sectional research of 576 older persons in an urban community in Shenzhen, China, who were 65 years of age or older [32] .…”
Section: Discussionsupporting
confidence: 90%
“…The ndings of this study were consistent with a number of earlier ndings, which indicated that frailty in the middle-aged and elderly Chinese population predicted the development of depressive symptoms [17,31] . Meanwhile, frailty was found to be a predictor of depressive symptoms in a cross-sectional research of 576 older persons in an urban community in Shenzhen, China, who were 65 years of age or older [32] .…”
Section: Discussionsupporting
confidence: 90%
“…Cao et al found that pre-frail and frail people, as defined by the frailty index and phenotype, are at a higher risk of developing depressive symptoms compared with those who are robust, based on a cohort study of 5303 older Chinese adults. 28 However, no effect of depressive symptoms on subsequent incidence of frailty was observed. Another 5-year follow-up study with 167 729 participants living in Netherlands demonstrated that depression and anxiety are reciprocally associated with frailty, as measured by the frailty index, in both younger and older adults.…”
Section: Discussionmentioning
confidence: 97%
“…Most existing studies have focused on investigating only one direction (either from depression to frailty or from frailty to depression), with very few examining the bidirectional association simultaneously, especially in a population‐based prospective design. Cao et al found that pre‐frail and frail people, as defined by the frailty index and phenotype, are at a higher risk of developing depressive symptoms compared with those who are robust, based on a cohort study of 5303 older Chinese adults 28 . However, no effect of depressive symptoms on subsequent incidence of frailty was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty was measured with a frailty index (FI), constructed from 30 indicators, including thirteen healthrelated diagnoses from physicians, five on disabilities, and twelve on limitations with activities of daily living (ADLs) and instrumental activities of daily living (IADLs) (see Supplemental Table 1). The indicators were selected following recommended procedures [33] and scored consistent with previous studies [7,[34][35][36][37][38][39]. The sum of the individual indicator scores was divided by 30 to create the FI (range: 0-1).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Prior studies highlighted the interrelationships among frailty, cognitive impairment, and depressive symptom among older adults living in China. More severe depressive symptoms were associated with a higher level of frailty [7], and frailty predicted incident depressive symptoms [8]. The one-year incidence of frailty is estimated to be 19.5% higher in older adults with cognitive impairment compared to those without cognitive impairment [9].…”
Section: Introductionmentioning
confidence: 99%